2018
DOI: 10.1080/11956860.2018.1513387
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral reactions of brown bears to approaching humans in Fennoscandia

Abstract: Human disturbance causes behavioral responses in wildlife, including large carnivores.Previous research in Scandinavia has documented that brown bears (Ursus arctos) show a variety of behavioral reactions to different human activities. We investigated how proximity to human settlements and roads, as proxies of human influence, affected brown bears' reactions to encountering humans. We analyzed experimental approaches to GPS collared bears, 18 males and 23 single females, in Sweden (n = 148 approaches) and Finl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Overall, both changepoint analysis and UCL performed similarly well for detecting flight initiation. Hence, as previous studies have shown, both can be used successfully to detect flight initiation (Moen et al, 2012(Moen et al, , 2018Ordiz et al, 2019;Viljanen, 2019). However, both methods have limitations, and neither performed flawlessly in our study.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Overall, both changepoint analysis and UCL performed similarly well for detecting flight initiation. Hence, as previous studies have shown, both can be used successfully to detect flight initiation (Moen et al, 2012(Moen et al, , 2018Ordiz et al, 2019;Viljanen, 2019). However, both methods have limitations, and neither performed flawlessly in our study.…”
Section: Discussionmentioning
confidence: 66%
“…In this study, UCL detected all flights which were also confirmed by visual inspection. However, Moen et al (2012Moen et al ( , 2018 reported cases in which visual inspection indicated a flight, but speed did not exceed the UCL. Changepoint analysis does not require control data, and it requires less data preparation, as it can handle various data distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this paper, we aimed to describe the flight response of seven wild GPS-collared wolves in Norway and Sweden by conducting experimental human approach trials. This is, to our knowledge, the first study assessing wolf flight responses toward humans with the use of high-resolution GPS data, which gives much more detailed and accurate information about flight intensity and flight patterns compared to VHF studies (Moen et al, 2012(Moen et al, , 2018Ordiz et al, 2019). High resolution GPS data makes it possible to re-construct details of the flight path without the need of snow tracking (Moen et al, 2012;Wam et al, 2012Wam et al, , 2014.…”
Section: Introductionmentioning
confidence: 97%
“…Responses to approaching humans have been studied previously in wolves using information from VHF-collars (Karlsson et al, 2007;Wam et al, 2012Wam et al, , 2014, and more recently in brown bears using high-frequency GPS data (Moen et al, 2012(Moen et al, , 2018Ordiz et al, 2019). In wolves, flight initiation distance (FID, i.e., the distance at which an animal flees from an approaching threat) was affected by wind conditions, with shorter FID when the wind was blowing away from the wolf, but not by horizontal visibility at the wolf 's location (Karlsson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%